Correlation of Health-Related Quality of Life in Clinically Stable Outpatients with Schizophrenia - Domenech C (Dove Medical Press, 2019)
Cristina Domenech,1,2 Adriana Pastore,3 A Carlo Altamura,4 Corrado Bernasconi,5 Ricardo Corral,6 Helio Elkis,7 Jonathan Evans,8 Ashok Malla,9 Francesco Margari,3 Marie-Odile Krebs,10 Anna-Lena Nordstroem,5 Mathias Zink,11 Josep Maria Haro1,2 1Universitat de Barcelona, Barcelona, Spain; 2Parc Sanitari Sant Joan de Déu, CIBERSAM, Institut de Recerca Sant Joan de Déu, Barcelona, Spain; 3Department of Basic Medical Science, Neuroscience and Sense Organs, ‘Policlinico’ Hospital, University of Bari ‘Aldo Moro’, Bari, Italy; 4University of Milan, Fondazione IRCCS Ca’ Granda, Ospedale Maggiore Policlinico, Milano, Italy; 5F. Hoffmann-La Roche Ltd, Basel, Switzerland; 6Fundación para el Estudio y Tratamiento de las Enfermedades Mentales (FETEM), Buenos Aires, Argentina; 7Departamento e Instituto de Psiquiatria – FMUSP, Sao Paulo, Brazil; 8Centre for Academic Mental Health, University of Bristol, Bristol, UK; 9Douglas Mental Health University Institute, McGill University, Montréal, QC, Canada; 10Service Hospitalo Universitaire, Laboratoire de Physiopathologie des Maladies Psychiatriques, Inserm, Université Paris Descartes, Hôpital Sainte-Anne, Paris, France; 11Central Institute of Mental Health, Department of Psychiatry and Psychotherapy, Medical Faculty Mannheim, Heidelberg University, Mannheim, Germany and Regional Clinical Centre, Ansbach, GermanyCorrespondence: Josep Maria HaroParc Sanitari Sant Joan de Déu - Antoni Pujadas, 42 - 08830 Sant Boi de Llobregat, Barcelona, SpainTel +34 93 600 26 85Email jmharo@pssjd.orgBackground: Generic health-related quality of life (HRQoL) scales are increasingly being used to assess the effects of new treatments in schizophrenia. The objective of this study is to better understand the usefulness of generic and condition specific HRQoL scales in schizophrenia by analyzing their correlates.Methods: Data formed part of the Pattern study, an international observational study among 1379 outpatients with schizophrenia. Patients were evaluated with the Mini International Neuropsychiatric Inventory, the Clinical Global Impression-Schizophrenia (CGI-SCH) Scale and the Positive and Negative Syndrome Scale (PANSS) and reported their HRQoL using the Schizophrenia Quality of Life Scale (SQLS), the Short Form-36 (SF-36), and the EuroQol-5 Dimension (EQ-5D). The two summary values of the SF-36 (the Mental Component Score and the Physical Component Score, SF-36 MCS and SF-36 PCS) were calculated.Results: Higher PANSS positive dimension ratings were associated with worse HRQoL for the SQLS, EQ-5D VAS, SF-36 MCS, and SF-36 PCS. Higher PANSS negative dimension ratings were associated with worse HRQoL for the EQ-5D VAS, SF-36 MCS, and SF-36 PCS, but not for the SQLS or the EQ-5D tariff. PANSS depression ratings were associated with lower HRQoL in all the scales. There was a high correlation between the HRQoL scales. However, in patients with more severe cognitive/disorganized PANSS symptoms, the SQLS score was relatively higher than the EQ-5D tariff and SF-36 PCS scores.Conclusion: This study has shown substantial agreement between three HRQoL scales, being either generic or condition specific. This supports the use of generic HRQoL measures in schizophrenia.Clinicaltrials.gov identifier: NCT01634542 (July 6, 2012, retrospectively registered).Keywords: schizophrenia, health-related quality of life, epidemiology, persistent symptoms